Continuity in features of anxiety and attention deficit/hyperactivity disorder in young preschool children - Overgaard, Kristin Romvig (Springer Berlin Heidelberg, 2014)
Anxiety disorders and attention deficit/hyperactivity disorder (ADHD) develop before school age, but little is known about early developmental pathways. Here we test two hypotheses: first, that early signs of anxiety and ADHD at 18 months predict symptoms of anxiety and ADHD at age 3½ years; second, that emotional dysregulation at 18 months predicts the outcome of co-occurring anxiety and ADHD at age 3½ years. The study was part of the prospective Norwegian Mother and Child Cohort Study (MoBa) at the Norwegian Institute of Public Health. The 628 participants were clinically assessed at 3½ years. Questionnaire data collected at 18 months were categorized into early behavioural scales of anxiety, ADHD, and emotional dysregulation. We investigated continuity in features of anxiety and ADHD from 18 months to 3½ years of age through logistic regression analyses. Anxiety symptoms at 3½ years were predicted by early signs of anxiety (Odds ratio (OR) = 1.41, CI = 1.15–1.73) and emotional dysregulation (OR = 1.33, CI = 1.15–1.54). ADHD symptoms at 3½ years were predicted by early signs of ADHD (OR = 1.51, CI = 1.30–1.76) and emotional dysregulation (OR = 1.31, CI = 1.13–1.51). Co-occurring anxiety and ADHD symptoms at 3½ years were predicted by early signs of anxiety (OR = 1.43, CI = 1.13–1.84), ADHD (OR = 1.30, CI = 1.11–1.54), and emotional dysregulation (OR = 1.34, CI = 1.13–1.58). We conclude that there were modest continuities in features of anxiety and ADHD through early preschool years, while emotional dysregulation at age 18 months was associated with symptoms of anxiety, ADHD, and co-occurring anxiety and ADHD at age 3½ years.